Effects of intensive lifestyle changes on the progression of mild cognitive impairment or early dementia due to Alzheimer’s disease: the need for rigor - Joshua D. Grill; Daniel Gillen (Alzheimer’s Research & Therapy)
Abstract We consider the recent publication by Ornish and colleagues and the rigor expected for interventional clinical trials. We contend that lifestyle intervention trials should strive for the same rigor as drug trials and highlight opportunities to improve rigor in this example, particularly in design, data analysis, and publication of results for this and other lifestyle intervention studies.